Prognostic risk factors of pneumonia associated with COVID-19 in patients with lymphoma - Liu, Dan; Yin, Xia; Wang, Hui; Xing, Lijie; Li, Ping; Wei, Haichen; Ma, Ji; He, Qiang; Xie, Linna; Lu, Ke; Li, Zengjun (Frontiers in Oncology, 2025)
ObjectivePatients with hematological malignancies have an elevated risk of developing pneumonia after contracting COVID-19. Lymphoma is the most prevalent hematologic malignancy. It is critical to identify patients at high risk of contracting COVID-19-associated pneumonia.MethodsFrom January 11–31, 2023, we distributed questionnaires to patients diagnosed with lymphoma according to 2016 World Health Organization diagnostic and classification criteria. COVID-19 infection was confirmed based on symptoms and laboratory tests. Pneumonia was confirmed using computed tomography scans.ResultsIn total, 257 patients were included in this study; 221 patients (86.0%) had COVID-19 infection and 61 (27.6%) of these had pneumonia. Patients with B-cell non-Hodgkin lymphoma (B-NHL) had a significantly higher pneumonia incidence than patients with other lymphoma types (31.8% vs. 27.6%, P=0.005). Higher incidence of pneumonia was observed in patients receiving anti-CD20 therapy (30.0% vs. 16.3%, P=0.048) and Bruton’s tyrosine kinase (BTK) inhibitor therapy (51.3% vs. 22.5%, P=0.001). B-NHL (hazard ratio [HR]=3.7, 95% confidence interval [CI] 1.4–10.0, P=0.009), anti-CD20 therapy (HR=2.3, 95% CI 1.0–5.2, P=0.050), BTK inhibitor (HR=3.6, 95% CI 1.8–7.4, P<0.001), active therapy (HR=3.0, 95% CI 1.5–5.7, P=0.001), and lack of disease remission (HR=3.7, 95% CI 1.8–7.4, P=0.001) were high-risk factors for developing pneumonia. Anti-PD-1 therapy was a protective factor against pneumonia development (HR=0.2, 95% CI 0.05–0.9, P=0.034). In multivariable analysis, BTK inhibitor (HR=3.5, 95% CI 1.6–8.0, P=0.003), active therapy (HR=3.3, 95% CI 1.6–6.8, P=0.001), and disease non-remission (HR=2.9, 1.3–6.4, P=0.007) were independent risk factors for pneumonia development after COVID-19 infection in patients with lymphoma.ConclusionsPatients with lymphoma receiving BTK inhibitors, undergoing active therapy, and lacking disease remission exhibited a higher risk for pneumonia associated with COVID-19.